Implementation of Performance Based Contracting in Malaysia - Anwar, Muhamad Firdaus; Shariff, Nur Diyana Md.; Chia, Teoh Chia; Jie, Lim Xin; Riazi, Salman Riazi Mehdi; Nawi, Mohd Nasrun Mohd (International Review of Management and Marketing, 2017)
Performance based contracting (PBC) has been used for several years in other countries. This procurement approach however can be considered new in Malaysia. In the past, this type of procurement was popular in lines such as production, maintenance, military, supply and service businesses. This paper studies about the challenges, benefits, tools, strategies and aspects of PBC that can be adopted from other countries and relates it for the purpose of improving Malaysian construction industry. Using outcomes from a series of open-ended interviews as well as from theoretical literature review, this paper also explores both success and failure factors of PBC and suggests a way in which it can be used in Malaysian construction industry. Finding from interviews indicates that Malaysian status of PBC implementation is not as expected. People are aware of PBC but the implementation is not well enough and it relates to the challenges from external and internal causes. However, tools like financial management and services improvement from PBC as well as encouragement and spread of awareness can be used to improve Malaysian construction industry. Keywords: Implementation, Benefit, Performance Based Contracting, Challenges, Improvement, Malaysia JEL Classifications: L24, M15